Method of “Active Correlations” for DSSSD detector application - Tsyganov, Yu. S. (Physics of particles and nuclei letters, 2015)
Real-time PC based algorithm is developed for DSSSD ( D ouble S ide S ilicon S trip D etector) detector. Brief description of the detection system is also presented. Complete fusion nuclear reaction nat Yt + 48 Ca → 217 Th is used to test this algorithm at 48 Ca beam. Example of successful application of a former algorithm for resistive strip PIPS (resistive strip P assivated I mplanted P lanar S ilicon) detector is presented too.